2003
DOI: 10.1128/cdli.10.1.19-21.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple Freeze-Thaw Cycles on Detection of Measles, Mumps, and Rubella Virus Antibodies

Abstract: We investigated the effect of multiple freeze-thaw cycles on mumps, measles, and rubella virus serum antibody levels with whole-virus immunoglobulin G enzyme-linked immunoassays. Fresh serum samples from nine healthy adult volunteers were divided into six sets of five aliquots each. Samples were taken through a total of 10 freeze-thaw cycles and stored at 4°C until assayed. Each assay measurement was done in replicates of five, and the mean value was reported. After completing 10 freeze-thaw cycles, we found n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 2 publications
5
30
2
Order By: Relevance
“…Long-term storage of serum samples at Ϫ20°C has been shown to decrease measured immunoglobulin G concentrations (26). However, storage at Ϫ80°C, as was done in this study, is considered the standard for samples to be assayed for immunoglobulin concentration and has not been associated with a decrease in immunoglobulin concentrations in other species (27,28); therefore, it is unlikely that this affected antibody concentrations in our study.…”
Section: Discussioncontrasting
confidence: 43%
“…Long-term storage of serum samples at Ϫ20°C has been shown to decrease measured immunoglobulin G concentrations (26). However, storage at Ϫ80°C, as was done in this study, is considered the standard for samples to be assayed for immunoglobulin concentration and has not been associated with a decrease in immunoglobulin concentrations in other species (27,28); therefore, it is unlikely that this affected antibody concentrations in our study.…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, other investigators found no significant effect on measured antibody levels or the ability to measure these antibodies by ELISA after completing 10 freeze-thaw cycles. 26 As all our samples had been through a maximum of two freeze-thaw cycles before, a general decline in the antibody levels could have occurred, but is less likely.…”
Section: Discussionmentioning
confidence: 96%
“…Other factors that can potentially affect ELISA results are temperature storage conditions and repeated freeze–thaw cycles. However, these affects appear to be less pronounced for ELISA detection of antibodies and viral antigens 1012. Further studies are required to determine the affect of other anticoagulant agents such as lithium heparin, sodium fluoride and potassium oxalate, as well as the affect of sample timing, on anticoagulant-treated samples on assay performance.…”
mentioning
confidence: 99%